Analysis of Service Quality, Trust and Commitment to Customer Satisfaction and Loyalty in Madura Batik Products - Moh Jufriyanto; Rifky Maulana Yusron (Universitas Trunojoyo Madura, 2019)
Batik is a part of Indonesian culture. Since long ago, Batik cloth is still a fabric representing Indonesian culture. Batik cloth is also a national cloth that provides special features for Indonesia. In this research conducting analysis of service quality, consumer confidence, commitment to customer satisfaction and customer loyalty in Madura batik products. The method used is PLS (Part Least Square). Models formed with PLS can be optimal in predictness accuracy has a large complexity and samples ranging from 30 to 100 samples. This research is done in one of the districts in Madura Island, Bangkalan regency. In the district Bangkalan many SME batik that sells Madura batik products. Samples of consumers taken as much as 100. his research consists of two models namely model 1 about service quality, consumer confidence, commitment to customer satisfaction. Model 2 on service quality, consumer confidence, and commitment towards customer satisfaction to customer loyalty. From the results of The value of coefficient of determination of model 1 is 0.888 or 88.8%. In Model 2 the value of coefficient of determination of the Model 2 is 0.906 or at 90.6%. From the hypothesis test results that from Models 1 and 2 that have a significant influence is the commitment variable, while other variables have no effect. From the measurement goodness of fit acquired that the Model 1 and 2 is said to be a good overall model prediction